APR-246 (PRIMA-1MET) strongly synergizes with AZD2281 (olaparib) induced PARP inhibition to induce apoptosis in non-small cell lung cancer cell lines. Issue 2 (1st June 2016) - Deben, Christophe; Lardon, Filip; Wouters, An; Op de Beeck, Ken; Van den Bossche, Jolien; Jacobs, Julie; Van Der Steen, Nele; Peeters, Marc; Rolfo, Christian; Deschoolmeester, Vanessa; Pauwels, Patrick
Highlights: APR-246 strongly synergizes with AZD2281 (olaparib). NOXA mRNA levels were only increased in a p53 mutant background. Treatment increased ROS levels and accumulation of γ-H2AX foci, leading to apoptosis. APR-246 restores mutant p53's transcriptional and mitochondrial function. Abstract: APR-246 (PRIMA-1 Met ) is able to bind mutant p53 and restore its normal conformation and function. The compound has also been shown to increase intracellular ROS levels. Importantly, the poly-[ADP-ribose] polymerase-1 (PARP-1) enzyme plays an important role in the repair of ROS-induced DNA damage. We hypothesize that by blocking this repair with the PARP-inhibitor AZD2281 (olaparib), DNA damage would accumulate in the cell leading to massive apoptosis. We observed that APR-246 synergistically enhanced the cytotoxic response of olaparib in TP53 mutant non-small cell lung cancer cell lines, resulting in a strong apoptotic response. In the presence of wild type p53 a G2/M cell cycle block was predominantly observed. NOXA expression levels were significantly increased in a TP53 mutant background, and remained unchanged in the wild type cell line. The combined treatment of APR-246 and olaparib induced cell death that was associated with increased ROS production, accumulation of DNA damage and translocation of p53 to the mitochondria. Out data suggest a promising targeted combination strategy in which the response to olaparib is synergistically enhanced by the addition of APR-246, especially in a TP53 mutant background.